PENGARUH KONEKSI POLITIK TERHADAP KINERJA PERUSAHAAN: Studi Empiris pada Perusahaan Sektor Pertambangan yang terdaftar di BEI tahun 2014-2018 - Azizah, Fajriatul’; Al Amin, Muhammad (Indonesian Journal of Accounting and Governance, 2020)
The company's financial condition can be described by the company's performance which is analyzedby various financial analysis measurement tools. The financial analysis is used to evaluate thecompany's financial condition as reflected by the company's performance in a period. The purpose ofthis study is to analyze the effect of political connections on company performance, especially inmining companies. Tobin's q is used as an indicator to measure company performance. This researchuse data from annual report of mining sector companies listed on the Stock Exchange Indonesia in2014-2018, which total 75 companies. Data collection method by purposive sampling method in orderto get representative sample criteria Hypothesis testing uses multiple linear regression analysis. Theresults of the study that political connections do not affect the company's performance, as measured bythe proportion of independent directors who have political connections.